Assessment of Nutritional Status of Young Adult Women Living in Slum Area of Indore City: Assessment of Nutritional Status and Health Education Needs of Young Adult Women in a Slum Area (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Introduction women health is greatly influenced by the nutritional intake,throughout the lifecycle good nutrition plays important role for proper physical growth and good health.Aim The aim of thestudy is to assess the nutritional status of young adult women who are more than 18 years of age, nonpregnantand unmarried. Method by random purposive sampling method of data collection, all women ofage 19-23 years were collected with their consent. Result it is clearly shown from obtained results that theeating habits of women is not good and their nutritional status was also poor. Conclusionwith theconsent of young adult women a proper nutrition and health education program is to be planned thatwould help them to become aware of their personal nutritional needs. Their knowledge regarding goodnutrition and health will carry forward to the next generation that would help to build a healthy individualas well as a healthy nation.